CONTEMPORARY CHALLENGES AND PERSPECTIVES OF BRAZILIAN ELECTORAL LAW: Abuse of Economic and Political Power in Electoral Campaigns (CIPEEX, 2025)
Brazilian electoral law currently faces new and complex challenges related to preserving the integrity of elections. Among them, the abuse of economic and political power in electoral campaigns stands out, practices that undermine equal opportunities for candidates and threaten the legitimacy of the democratic process. This study aims to analyze the main case law on the subject and reflect on its impacts on the electoral system, focusing on the measures adopted by the Superior Electoral Court (TSE) to curb these practices. The methodology used consisted of bibliographical and documentary research, with the analysis of recent judgments. It was found that, despite legislative and judicial advances, significant challenges remain in the effectiveness of punishments and the timely identification of illegal conduct. It is concluded that strengthening oversight mechanisms and raising public awareness are fundamental to consolidating democracy in Brazil.
Keywords: CLEAN RECORD; ELECTORAL DISINFORMATION; LEGISLATIVE REFORMS; ELECTION FAIRNESS; ELECTORAL OVERSIGHT MECHANISMS; REVOCATION OF MANDATES; INRLIGIBILITY